Pengaruh Citra Merek Dan Kualitas Produk Terhadap Minat Beli Be Rych Water Di Aceh - Silva Aulia Salsabila (Indo Publishing, 2026)
This study aims to analyze the influence of brand image and product quality on consumer purchase intention of Be Rych Water in West Aceh Regency, both partially and simultaneously. The increasing competition in the bottled drinking water industry requires local companies to strengthen their marketing strategies through the development of a positive brand image and improvement of product quality to compete with national brands. This research employs a quantitative approach using a survey method by distributing questionnaires to 100 respondents who are consumers of Be Rych Water. The data were analyzed using multiple linear regression with the SPSS version 26.0 program, accompanied by validity, reliability, and classical assumption tests to ensure data accuracy and consistency. The results show that brand image has a positive and significant effect on purchase intention, indicating that the stronger the brand image, the greater the consumer’s desire to purchase the product. Product quality also has a significant effect on purchase intention, where high-quality products can foster consumer trust, satisfaction, and loyalty. Simultaneously, brand image and product quality have a significant influence on purchase intention with an R² value of 0.873, indicating that 87.3% of the variation in purchase intention can be explained by these two variables, while the remaining 12.7% is influenced by other factors such as price, promotion, and personal preference. This study supports the theory of Kotler and Keller (2022), which emphasizes that brand perception and product quality are key determinants in shaping consumer purchasing decisions.